Reikai Kanyouku Idiom “Kuchi” Dalam Website Kotobank.jp - Aditya Himawan; Novi Andari (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2021)
Kanyouku is a phrase that only has an idiomatic meaning, the meaning cannot be known even if we understand the meaning of each word that makes up the phrase. The focus of this research is on classifying kanyouku using the word kuchi on the kotobank.jp website into the classification of the meaning of kanyouku. The method used is descriptive qualitative with data collection techniques used taking note method. The data found are 35 data which are empirical data. The results of this study show that based on 5 classifications of kanyouku meaning, in kankaku, kanjou wo arawasu kanyouku (感覚・感情を表す慣用句) found 4 data. In karada, seikaku, taido wo arawasu kanyouku (体・性格・態度を表す慣用句) 16 data were found. In Joutai, teido, kachi wo arawasu kanyouku (状態・程度・価値を表す慣用句) no data were found related to this kanyouku classification. In koui, dousa, koudou wo arawasu kanyouku (好意・動作・行動を表す慣用句) 15 data were found. In Shakai, bunka, seikatsu wo arawasu kanyouku ) no data were found related to this kanyouku classification. The meaning of kanyouku contained in the data source states things related to social life in society where there are individuals with various characters, emotions, activities or movements carried out by community members both individually and in small groups in it. The use of idioms in conversation as an indirect form of satire.